A new species of Barbatula from the headwaters of the Bulgan River in western Mongolia (Teleostei: Nemacheilidae) - Prokofiev, Artem M. (Zootaxa, 2018)
Barbatula karabanowi, new species, is described from the upper Bulgan River drainage in Mongolia. It is most similar to B. dsapchynensis from the Zavhan River basin (Lake Valley, Mongolia). The new species is distinguished from this and all other species of Barbatula in Asia by a combination of characters, none of them unique: nostrils widely spaced; snout broad, ratio between maximum head width and width of snout at anterior nare 1.4–1.6; lips smooth, upper lip with a short incision; lower lip with short, well developed lateral lobes, mental lobes oval, lacking conical protrusions; scales absent or isolated scales present on the flank between dorsal- and caudal-fin bases; 42–44 vertebrae (usually 43); 75–88 lateral line pores on flank; paired fins with rounded tips; pigmentation pattern with densely set and partially fused irregularly shaped blotches and streaks. Barbatula karabanowi occurs in syntopy with B. cf. altayensis. It is distinguished from this species by having widely separated nares (vs. closely-set), details in the mouth structure, few or no scales (vs. squamation well developed), less vertebrae and lateral line pores (42–44 and 75–88 vs. 44–45 and 89–105, respectively), “non-muscular” cheeks in both sexes (vs. thickened, especially in the males) and details in colour pattern. These two species were found to prey on different food items and were the only fish taxa found in the studied part of the river.